Electrochemical degradation of polycyclic aromatic hydrocarbons in synthetic solution and produced water using a Ti/SnO2-Sb2O5-RuO2 anode - Yaqub, A. (American Society of Civil Engineers (ASCE), 2015)
Electrochemical-oxidation experiments was conducted for degradation of 16 priority polycyclic aromatic hydrocarbons (PAHs) using a dimensionally stable anode (DSA)-type Ti/SnO2-Sb2O5-RuO2 electrode. In the research reported in this paper, for electrooxidation, anode was coated with metal oxides SnO2, Sb2O5, and RuO2 in laboratory using titanium as substrate dip coating thermal decomposition method. Laboratory-scale batch reactor was used for degradation studies at pH 3, 6, and 9. Surface morphology and composition of the anode coatings were characterized by variable pressure field emission scanning electron microscopy and energy dispersive X-ray spectroscopy, respectively. Coating microstructure was analyzed by X-ray diffraction. Stability of coating was analyzed by Raman spectroscopy. Gas chromatography-mass spectrometry results revealed that almost 80, 73, and 82 PAHs removal was found without using electrolyte at pH 3, 6, and 9, respectively. While using electrolyte removal efficiency gone to 93, 87, and 93 at pH 3, 6, and 9, respectively. To study the optimum conditions for electrochemical degradation of PAHs from produced water, Box-Behnken design was used. Experiments were designed for each anode as function of independent variables such as current density, pH, and electrolysis time. Quadratic model was suggested best-fit model. The results of the ANOVA for PAHs revealed that the model was highly significant. Â© 2014 American Society of Civil Engineers.